Responsabilidad del adulto mayor desamparado causante de accidente de tránsito en área rural. - Gómez, Edison G. (2022)
The Comprehensive Organic Criminal Code (COIP) article 373, establishes the criminal responsibility of pedestrians, passengers, driver, or another person when he is responsible for an accident and not the driver of a vehicle, sanctioning him with the penalties provided and the circumstances of the offense. For its part, article 265 of the Regulation to the Law of Land Transport, Traffic and Road Safety, establishes that pedestrians who are pedestrians are adults over sixty-five years of age will have the right to have the necessary help from responsible persons and especially from traffic officers, when crossing public roads. It is necessary to attend in a transversal way through this research the guarantee and protection of the rights of the elderly in situations of vulnerability and risk. traffic agent and that when crossing the public road is the cause of a traffic accident, can he find himself immersed in the responsibility provided for in article 373 of the COIP? Through doctrinal analysis and statistics on road accidents, conclusions are reached on the responsibility of the State in the protection of the elderly.